Pre-transplant immune profile defined by principal component analysis predicts acute rejection after kidney transplantation - Gaiffe, Emilie; Colladant, Mathilde; Desmaret, Maxime; Bamoulid, Jamal; Leroux, Franck; Laheurte, Caroline; Brouard, Sophie; Giral, Magali; Saas, Philippe; Courivaud, Cécile; Degauque, Nicolas; Ducloux, Didier (Frontiers in Immunology, 2023)
Background Acute rejection persists as a frequent complication after kidney transplantation. Defining an at-risk immune profile would allow better preventive approaches. Methods We performed unsupervised hierarchical clustering analysis on pre-transplant immunological phenotype in 1113 renal transplant recipients from the ORLY-EST cohort. Results We identified three immune profiles correlated with clinical phenotypes. A memory immune cluster was defined by memory CD4+T cell expansion and decreased naïve CD4+T cell. An activated immune cluster was characterized by an increase in CD8+T cells and a decreased CD4/CD8 ratio. A naïve immune cluster was mainly defined by increased naïve CD4+T cells. Patients from the memory immune profile tend to be older and to have diabetes whereas those from the activated immune profile were younger and more likely to have pre-transplant exposure to CMV. Patients from the activated immune profile were more prone to experience acute rejection than those from other clusters [(HR=1.69, 95%IC[1.05-2.70], p=0.030) and (HR=1.85; 95%IC[1.16-3.00], p=0.011). In the activated immune profile, those without previous exposure to CMV (24%) were at very high risk of acute rejection (27 vs 16%, HR=1.85; 95%IC[1.04-3.33], p=0.039). Conclusion Immune profile determination based on principal component analysis defines clinically different sub-groups and discriminate a population at high-risk of acute rejection.